FC 123RENAL TRANSPLANTATION MITIGATES INCREASED BIOLOGICAL (EPIGENETIC) AGE IN CHRONIC KIDNEY DISEASE. (29th May 2021) - Neytchev, Ognian; Witasp, Anna; Nordfors, Louise; Qureshi, Abdul Rashid Tony; Wennberg, Lars; Erlandsson, Helen; Ebert, Thomas; Selman, Colin; Shiels, Paul; Stenvinkel, Peter
Abstract: Background and Aims: Chronic kidney disease (CKD) shares important features of a dysregulated ageing process with other common "burden of lifestyle" diseases, which aggregates into the diseasome of ageing. Typically, this is hallmarked by an acceleration of epigenetic (DNA methylation-based) clocks. It remains to be determined if current therapeutic interventions, such as renal transplantation or dialysis, can slow this clock, and thus the rate of biological ageing, in CKD. We therefore assessed the rate of biological ageing in CKD patients and whether these therapies impact on it, by measuring epigenetic age before and 1 year after treatment. Methods: Whole blood samples were taken from CKD 5 patients at baseline and 1 year after renal transplantation (n=12) or dialysis (n=11; peritoneal dialysis n=7, haemodialysis n=4) as well as from age and sex-matched population-based controls (n=24). DNA methylation was measured using the Illumina Infinium Human Methylation 450K BeadChip and epigenetic age was calculated using three independent DNA methylation clocks: the Horvath, Hannum, and PhenoAge clocks. Additionally, a novel composite clock incorporating these three clocks was evaluated. We then calculated the age acceleration (difference between epigenetic and chronological age) for each clock and compared average age acceleration between groups and across time points. Results: Incident dialysis patients displayed accelerated ageing versus chronologically age-matched controls (p<0.001). We observed a PhenoAge age acceleration difference in both the transplant (8.5 years, p=0.001) and dialysis (9.7 years, p<0.001) groups at baseline compared to control. After 1 year, we also observed a decrease of the age acceleration in the transplant group (mean reduced by 4.4 years, p=0.016), but not in the dialysis group (mean reduced by 0.7 years, p=0.668). Conclusion: CKD 5 patients display an increased biological (i.e. epigenetic) age. This age acceleration is mitigated one year after renal transplantation, but not in patients undergoing dialysis. Neither therapy reverses high biological age.